1988
DOI: 10.1002/bjs.1800751217
|View full text |Cite
|
Sign up to set email alerts
|

Local thrombolytic therapy of acute peripheral arterial ischaemia with tissue plasminogen activator: A dose-ranging study

Abstract: Low-dose streptokinase has been established as an alternative to surgery in selected patients with acute peripheral arterial ischaemia. Tissue plasminogen activator (t-PA) is responsible for normal plasma fibrinolytic activity and has recently become available for clinical use owing to recombinant DNA technology. It has the theoretical advantage of fibrin specificity, which may result in enhanced thrombolytic effects with greater safety. Twenty-three patients with recent lower limb arterial occlusions received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Further studies confirmed that a much lower dose (0.05 mg/h) is adequate to achieve the same therapeutic effect. 11,31,32 In two randomized trials, the limb salvage rate was significantly higher with rt-PA than with either SK (80 vs. 60%) or UK (50 vs. 37%). 33,34 Several nonrandomized trials of IAT in subacute occlu sions found shorter lysis time with rt-PA without higher complication rates.…”
Section: Thrombolytic Drugs/clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies confirmed that a much lower dose (0.05 mg/h) is adequate to achieve the same therapeutic effect. 11,31,32 In two randomized trials, the limb salvage rate was significantly higher with rt-PA than with either SK (80 vs. 60%) or UK (50 vs. 37%). 33,34 Several nonrandomized trials of IAT in subacute occlu sions found shorter lysis time with rt-PA without higher complication rates.…”
Section: Thrombolytic Drugs/clinical Resultsmentioning
confidence: 99%
“…33,34 Several nonrandomized trials of IAT in subacute occlu sions found shorter lysis time with rt-PA without higher complication rates. [30][31][32][35][36][37][38] Another great advantage of rt-PA is the short half-life of 1.5 minutes, which allows any subsequent surgical procedure to be performed im mediately after IAT. Thus, rt-PA has become the thrombo lytic agent of choice for IAT in ALLI.…”
Section: Thrombolytic Drugs/clinical Resultsmentioning
confidence: 99%
“…A dose-ranging study for rtPA by Earnshaw et al [38] compared rtPA with low-dose SK. rtPA was effective in all concentrations studied from 0.25 mg/hr to 2.5 mg/hr, and duration of lysis was shorter than with SK.…”
Section: Thrombolytic Agentsmentioning
confidence: 99%
“…Risius and Graor (1) have compared 0.1 mg kg-1 h-l to 0.05 mg kg-1 h-1 rt-PA continuous infusion rates and selected the lowest. Other pilot studies (2,3,4) have proposed rt-PA dosages between 0.25 mg 6-r up to 10 mg 6-t. The mean infusion time was 5 h to 29 hand a successful clot lysis occurred in 80o/" to 100% of the cases.…”
mentioning
confidence: 99%
“…The mean infusion time was 5 h to 29 hand a successful clot lysis occurred in 80o/" to 100% of the cases. More major bleeding complications were found in patient groups with higher doses (2,3) Expecting that shortening the infusion time could reduce the bleeding risk even with higher doses of thrombolytic drugs and that bolus injections could be more efficient than continuous infusions, we have developed a 2-stage procedure combining bolus and continuous infusion.…”
mentioning
confidence: 99%